AN ANALYSIS OF GRAMMATICAL ERROR ANALYSIS IN USING SIMPLE PAST TENSE IN WRITING RECOUNT TEXT MADE BY EIGHTH GRADE STUDENTS OF SMP N 1 TEJAKULA - ., Komang Adi Arta; ., Ni Komang Arie Suwastini, S.Pd,M.Hum.; ., Drs. Asril Marjohan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study was a descriptive qualitative research which aimed at analyzing the grammatical error and the source of grammatical errors in writing a recount text. The subjects of this research were the eighth grade students of SMP N 1 Tejakula. The data were presented in the descriptive analysis way and the procedure of the error analysis used according to Dulay et al (1982). The result of the study the highest errors made by the students were in the errors of selection consisting of 172 errors or 71.4%. It was followed by the errors of omission consisting of 48 errors or 19.9%. Then, it was followed by the errors of addition consisting of 14 errors or 5.8% and the lowest errors were the errors of ordering consisting of 7 errors or 2.9%. The data also indicated that the inter-lingual transfer was the highest source of the errors. Based on the result, it can be concluded that the error of selection is the highest error made by the students and inter-lingual transfer is the highest source of error because it was caused by the mother tongue interference. Kata Kunci : Error analysis, simple past tense, recount text Penelitian ini adalah deskriptif qualitative yang bertujuan untuk menganalis kesalahan grammar dan sumber kesalahan dalam menulis teks recount. Subjek dari penelitian ini adalah siswa kelas 8 SMP N 1 Tejakula. Data disajikan dengan cara deskriptif analisis dan langkah-langkah yang digunakan untuk menganalisis kesalahan adalah teori dari Dulay et al (1982). Hasil dari penelitian ini menunjukakan bahwa kesalahan tertinggi yang dibuat oleh siswa adalah kesalahan selection yaitu 172 kesalahan atau 71,4 persen. Diikuti oleh kesalahan omission yaitu 48 kesalahan atau 19,9 persen. Kemudian diikuti oleh kesalahan addition yaitu 14 kesalahan atau 5,8 persen. Dan kesalahan yang paling sedikit adalah kesalaan ordering yaitu 7 kesalahan atau 2,9 persen. Data ini juga menunjukkan bahwa Inter-lingual transfer adalah sumber kesalahan tertinggi. Dari hasil di atas dapat disimpulkan bahwa kesalahan selection adalah kesalahan yang paling tinggi dibuat oleh siswa dan inter-lingual transfer adalah sumber kesalahan tertinggi karena disebabkan pengaruh dari bahasa ibu.keyword : analisis kesalahan, simpe past tense, teks recount